A new species of Gastrosaccus (Crustacea, Mysidacea) from Algoa Bay (South Africa) - Deprez, T.; Wooldridge, T.; Mees, J. (Hydrobiologia, 2000)
Gastrosaccus wittmanni sp. nov. was collected from surface-waters near Kings Beach in Algoa Bay (South Africa). Morphologically, it is characterised by having seven strong spines on each side of the telson. In between the storng spines, spinules are present except between the first most proximal pair. The endopod of the first female pleopod bears one terminal plumose seta. Most of the setae on antennules, antennae, thoracopods, pleopods and uropods are jointed.
NeMys doc_id: 3555